Anthocyanins and Anthocyanin Biosynthesis Gene Expression in Passiflora Flower Corona Filaments - Eliana Nutricati; Erika Sabella; Carmine Negro; Samar Min Allah; Andrea Luvisi; Luigi De Bellis; Rita Annunziata Accogli (Plants)
The diversity in anthocyanin flower pigmentation is vital in the ornamental plant market. To understand the regulation of the corona filament pigmentation of the Passiflora flower, we investigated the anthocyanin profiles of five distinct species (P. violacea, P. caerulea, P. edulis, P. incarnata, and P. coccinea) using HPLC-MS. A total of 14 anthocyanins, differentially distributed in the analyzed species, were identified as responsible for the differences in corona color, which can be attributed to different ratios of pelargonidin, cyanidin, and delphinidin. Additionally, we evaluated the expression of some biosynthetic genes, including dehydroflavonol reductase (DFR), flavonoid 3′-hydroxylase (F3′H), and flavonoid 3′,5′-hydroxylase (F3′5′H). F3′H seems to regulate the accumulation of cyanidins, F3′5′H determines blue pigmentation, and DFR enhances the biosynthesis of pelargonidins. Furthermore, three genes coding for key transcription factors, Myeloblastosis (MYB), basic helix-loop-helix (bHLH), and WD repeat protein (WD40), were examined using qPCR. The results confirm that such genes regulate anthocyanin biosynthesis and provide insight into the molecular mechanisms that underlie pigment biosynthesis for application in biotechnologies.